Evaluation of a particle enhanced turbidimetric assay for the measurement of neutrophil gelatinase-associated lipocalin in plasma and urine on Architect-8000: Analytical performance and establishment of reference values - Makris, K.; Stefani,D.; Makri,E.; Panagou,I.; Lagiou, M.; Sarli,A.; Lelekis,M.; Kroupis, C. (Clin.Biochem., 2015)
OBJECTIVES: Neutrophil gelatinase-associated lipocalin (NGAL) is a promising biomarker for acute kidney injury. NGAL can be measured in both blood and urine. Apart from kidney injury, NGAL levels in both plasma and urine can be influenced by various pathological situations. Accurate evaluation and comparison of results deriving from clinical studies require robust assays, appropriate specimen handling and reference intervals that will reflect its levels in a healthy population for both biological matrices. METHODS: We report the analytical validation of a latex particle-enhanced turbidimetric immunoassay (PETIA) aimed to measure NGAL in plasma and urine on an automated biochemistry analyzer (ABBOTT-Architect-8000). Assay performance characteristics were evaluated using standard protocols. Urine and plasma specimen storage requirements were determined and reference ranges for blood and urine were determined using healthy controls. RESULTS: The assay is precise (total CV%<4.8%), and sensitive (limit of quantification: 8.4 ng/mL for plasma and 9.0 ng/mL for urine), showing no hook effect. Calibration is stable for at least 30 days. The assay showed excellent linearity over the studied interval (20-4450 ng/mL). The analyte is stable at 4 degrees C for at least 5 days, and at 20 degrees C for 4h. Gender specific reference ranges for plasma (male: 38.7-157.6 ng/mL, female: 24.4-142.5 ng/mL) and unisex for urine (<9.0-49.41 ng/mL) are proposed. CONCLUSION: Our data indicate that NGAL can be measured with adequate precision and sensitivity on automated biochemistry analyzers and its measurement could easily be added to a standard panel to screen kidney diseases
DA - 20151215 IS - 1873-2933 (Electronic) IS - 0009-9120 (Linking) LA - eng PT - Journal Article SB - IM